Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes. (15th February 2023) - Zhang, Qiang; Hu, Wei; Ren, Hong; Yang, Jianbo; Deng, Junjun; Wang, Dawei; Sun, Yele; Wang, Zifa; Kawamura, Kimitaka; Fu, Pingqing
Abstract: The land-sea breeze circulation significantly impacts the atmospheric transport of organic aerosols in coastal regions. However, the links between organic aerosols and land-sea breezes remain poorly understood. In this study, organic marker compounds for biomass burning, primary biological aerosols, biogenic and anthropogenic secondary organic aerosols (SOA) in fine particles from a coastal city in East China were analysed using gas chromatography–mass spectrometry. Land-sea breeze circulations were identified to explore their potential influence on organic molecular compositions. Organic marker compounds showed obvious diurnal/seasonal patterns. Surprisingly, due to the combined influence of weakened East Asian monsoons and land-sea breezes, all detected organic markers decreased except α/β-pinene SOA markers during land-sea breeze periods in early autumn; whereas, all the organic markers increased except α/β-pinene SOA markers, pollen and plant debris markers during land-sea breeze periods in early spring. Furthermore, the reaction pathway and aging of biogenic SOA were also related to land-sea breezes. During the land-sea breeze periods, the ratios of 2-methylglyceric acid (2-MGA) to 2-methyltetrols increased in early autumn, indicating that more isoprene-derived SOA generated from the high-NO x (nitrogen oxides) pathway when the land-sea breezes occurred; while the ratios decreased in early spring, this may be related to the chemical transformation of 2-MGA to 2-MGA sulfates. Changes in the ratio of monoterpene SOA markers demonstrate that monoterpene SOA was relatively aged during sea breeze periods, while it was fresher when the land breeze occurred. Although boundary layer height, emissions, gas/particle partitioning, etc. are important reasons for the diurnal variations of organic aerosols, night/day ratios of molecular markers increased obviously when land-sea breezes occurred in both early autumn and early spring. Our results provide new insights into the shift in the chemical composition of organic aerosols over coastal areas that are influenced by land-sea breezes. Graphical abstract: Image 1 Highlights: The sources of coastal organic aerosols exhibit obvious diurnal and seasonal differences. Land-sea breezes impact on abundance and chemical composition of coastal aerosols. The reaction pathway and aging of biogenic SOA are related to land-sea breezes.